Ultralow-temperature superplasticity and its novel mechanism in ultrafine-grained Al alloys. Issue 11 (2nd November 2021) - Chinh, Nguyen Q.; Murashkin, Maxim Yu; Bobruk, Elena V.; Lábár, János L.; Gubicza, Jenő; Kovács, Zsolt; Ahmed, Anwar Q.; Maier-Kiener, Verena; Valiev, Ruslan Z.
Abstract : The important benefits of ultrafine-grained (UFG) alloys for various applications stem from their enhanced superplastic properties. However, decreasing the temperature of superplasticity and providing superplastic forming at lower temperatures and higher strain rates is still a priority. Here, we disclose, for the first time, the mechanism by which grain boundary sliding and rotation are enhanced, when UFG materials have grain boundary segregation of specific alloying elements. Such an approach enables achieving superplasticity in commercial Al alloys at ultralow homologous temperatures below 0.5 (i.e. below 200°C), which is important for developing new efficient technologies for manufacturing complex-shaped metallic parts with enhanced service properties. IMPACT STATEMENT: For the first time, ultralow-temperature superplasticity is found in commercial 7xxx Al alloy. This discovery enables the development of new technologies for the superplastic forming of complex-shaped products with enhanced service properties.